Pramipexole enhances disadvantageous decision-making: Lack of relation to changes in phasic dopamine release - Pes, R; Godar, S; Fox, A; Burgeno, L; Strathman, H; Jarmolowicz, D; Devoto, P; Levant, B; Phillips, P; Fowler, S; Bortolato, M (Elsevier, 2016)
Pramipexole (PPX) is a high-affinity D2-like dopamine receptor agonist, used in the treatment of Parkinson's disease (PD) and restless leg syndrome. Recent evidence indicates that PPX increases the risk of problem gambling and impulse-control disorders in vulnerable patients. Although the molecular bases of these complications remain unclear, several authors have theorized that PPX may increase risk propensity by activating presynaptic dopamine receptors in the mesolimbic system, resulting in the reduction of dopamine release in the nucleus accumbens (NAcc). To test this possibility, we subjected rats to a probability-discounting task specifically designed to capture the response to disadvantageous options. PPX enhanced disadvantageous decision-making at a dose (0.3 mg/kg/day, SC) that reduced phasic dopamine release in the NAcc. To test whether these modifications in dopamine efflux were responsible for the observed neuroeconomic deficits, PPX was administered in combination with the monoamine-depleting agent reserpine (RES), at a low dose (1 mg/kg/day, SC) that did not affect baseline locomotor and operant responses. Contrary to our predictions, RES surprisingly exacerbated the effects of PPX on disadvantageous decision-making, even though it failed to augment PPX-induced decreases in phasic dopamine release. These results collectively suggest that PPX impairs the discounting of probabilistic losses and that the enhancement in risk-taking behaviors secondary to this drug may be dissociated from dynamic changes in mesolimbic dopamine release.